2018
DOI: 10.1055/s-0038-1660832
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise on Breast Cancer–Related Lymphedema: What the Lymphatic Surgeon Needs to Know

Abstract: Several forms of exercise appear to be safe interventions for clinicians to use when treating this population and offer benefits such as improved quality of life, strength, body mass index, and mental health and decreased pain and lymphatic swelling. Additional research should be conducted to further examine the efficacy and safety of nontraditional forms of exercise in the treatment of BCRL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 36 publications
(61 reference statements)
0
49
1
1
Order By: Relevance
“…Traditionally, patients with lymphedema or who are at risk for lymphedema tend to reduce physical exercise due to concerns about disease exacerbation (100). Some preliminary studies have indicated that exercise neither causes lymphedema nor worsens the disease (101)(102)(103)(104)(105). A slowly progressive weight-lifting program does not increase the rate of lymphedema compared with no exercise, and aerobic exercise, resistance training, stretching, yoga, qigong and pilates are also safe (101,105).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, patients with lymphedema or who are at risk for lymphedema tend to reduce physical exercise due to concerns about disease exacerbation (100). Some preliminary studies have indicated that exercise neither causes lymphedema nor worsens the disease (101)(102)(103)(104)(105). A slowly progressive weight-lifting program does not increase the rate of lymphedema compared with no exercise, and aerobic exercise, resistance training, stretching, yoga, qigong and pilates are also safe (101,105).…”
Section: Treatmentmentioning
confidence: 99%
“…Some preliminary studies have indicated that exercise neither causes lymphedema nor worsens the disease (101)(102)(103)(104)(105). A slowly progressive weight-lifting program does not increase the rate of lymphedema compared with no exercise, and aerobic exercise, resistance training, stretching, yoga, qigong and pilates are also safe (101,105). Under specific circumstances, resistance training can even substantially improve the lymphedema state and may prevent the development of secondary lymphedema in patients (106).…”
Section: Treatmentmentioning
confidence: 99%
“…[18][19][20] Practicing different physical exercises such as aerobics, endurance exercises, stretching, yoga, qi gong, and Pilates have proved to be safe and efficient in the management of symptoms in patients with lymphedema or with a risk of developing it, according to a systematic review of 26 articles carried out recently. 21 However, the therapeutic myolymphokinetic exercises have greater visibility since they are found in CDT and were performed in this study in compliance with a protocol of gradual warm up of muscle chains, exercises for increased joint range and muscle stretching and relaxation. 22 According to a systematic review about manual lymphatic drainage for lymphedema after breast cancer, the technique is considered to be safe and well tolerated, but there is a lack of studies that used only drainage for group comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, is adipogenesis a direct outcome of lymphedema or is it indirectly caused by chronic immobility that is associated with lymphedema? This important question was addressed in part by recent studies, which have suggested that exercise (yoga, stretching, strength training) could improve breast cancer-related lymphedema (Baumann et al, 2018;Panchik et al, 2019). These studies must be very encouraging to lymphedema patients as they suggest that lymphedema-associated adipogenesis could be controlled by exercise.…”
Section: Clinical Correlations Between Obesity and Lymphedemamentioning
confidence: 99%